2022
DOI: 10.4081/jphr.2021.2256
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in New Diagnosis of HIV/AIDS in the Two Years Period 2019-2020: Impact of COVID-19 Pandemic

Abstract: The emergence SARS-CoV-2 in late 2019 and early 2020 has caused a pandemic of unprecedented proportions. Management of COVID-19 became emergent public health priorities, and the impact on other public health initiatives, such as expanded HIV screening and linkage to care, remain largely unknown. In this Single-Center retrospective observational study, we describe the characteristics and circumstance of the new HIV cases during 2020 compared to 2019. We observed a decrease of HIV diagnosis during this period. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Due to shifting healthcare restrictions, lockdowns and travel bans worldwide, a large number of migrant populations might not have been able to reach our ED. The impact of the pandemic reducing the number of HIV diagnoses has also been reported by other groups in multiple countries [48–53]. Regarding late diagnosis and missed opportunities, data from 12 September 2018 to 11 September 2019 are unaffected by the COVID‐19 pandemic and still show a reduction in late diagnosis, mean number of previous healthcare encounters and percentage of patients with at least one healthcare encounter, all of which hints favourably at the benefit of our intervention.…”
Section: Discussionsupporting
confidence: 70%
“…Due to shifting healthcare restrictions, lockdowns and travel bans worldwide, a large number of migrant populations might not have been able to reach our ED. The impact of the pandemic reducing the number of HIV diagnoses has also been reported by other groups in multiple countries [48–53]. Regarding late diagnosis and missed opportunities, data from 12 September 2018 to 11 September 2019 are unaffected by the COVID‐19 pandemic and still show a reduction in late diagnosis, mean number of previous healthcare encounters and percentage of patients with at least one healthcare encounter, all of which hints favourably at the benefit of our intervention.…”
Section: Discussionsupporting
confidence: 70%
“…With data from 225 HIV treatment sites across 42 countries at the end of the first year of the COVID-19 pandemic, this study found that most had experienced disruptions in clinic operations and in the provision of HIV care. Such disruptions were reported by sites across high-, medium-and low-HIV prevalence settings and country income levels, reinforcing concerns raised by modelling studies [9,[11][12][13] and observational research [41][42][43][44][45][46][47][48][49] about the potential of COVID-19 to reverse progress towards 95-95-95 UNAIDS targets to end the HIV epidemic, particularly in settings with a high HIV burden [50].…”
Section: Discussionmentioning
confidence: 99%
“…While clinics in high-prevalence settings were less http://onlinelibrary.wiley.com/doi/10.1002/jia2.26036/full | https://doi.org/10.1002/jia2.26036 likely to report suspending HIV services and appointments, other care-seeking barriers (e.g. lockdown restrictions, transportation and financial barriers, and concerns about COVID-19 exposure) may have presented insurmountable obstacles for patients in these settings, and early data from diverse settings have highlighted sharp decreases in healthcare-seeking for HIV-related services early in the pandemic, including HIV prevention [49,53], diagnosis [24,41,42,[44][45][46][47][48][53][54][55] and treatment [24,43,44,53,55,56], as well as diagnostics and treatment for other infectious diseases and chronic conditions [55][56][57][58]. While some studies in sub-Saharan Africa have reported rebounds in HIV testing and ART initiation [24,59], our findings related to stockouts of second-and third-line ART regimens in high-prevalence and low/lower-income settings are concerning, as the lack of such essential medicines may result in setbacks for both HIV treatment and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 years (March 2020 to February 2022), we could have lost around 517, 115 and 37 new diagnoses of hrHPV, HCV and HIV respectively. Several studies suggest that a decrease in the hrHPV, HCV, HIV detection after the pandemic could lead to higher cancer mortality (15,16) and a lower life expectancy for AIDS-defining conditions (17) in the following years. The delay in the HIV diagnosis is associated with non-infectious comorbidities and multimorbidity and contributes to higher total care costs (7).…”
Section: Discussionmentioning
confidence: 99%